ANALISIS PEMANFAATAN MARKETPLACE DALAM MENINGKATKAN PENDAPATAN BAGI PENJUALAN PRODUK UMKM DI KOTA LANGSA - Tarlis, Andi; Novita, Mutia; Rona, Riza (JSI: Jurnal Saudagar Indonesia, 2025)
Information technology that is developing so rapidly has brought major changes to all fields, including the economic/business sector. The digital era and the increasing number of internet users provide various conveniences in various activities. The research entitled Analysis of Marketplace Utilization in Increasing Income for Sales of MSME Products in Langsa City. This type of research uses qualitative. The formulation of the research problem is 1) how is the use of the marketplace on Facebook media in increasing revenue for the sale of MSME products in Langsa City, 2) what are the impacts of using the marketplace on Facebook media on the economy of MSME actors in Langsa City. The results of the study are 1) The use of the online marketplace media on Facebook has a huge impact on the sales income of business people, especially for Micro, Small and Medium Enterprises in Langsa Barat District, Langsa City. With the support and assistance from the Langsa City Government for micro business actors in order to increase their production and sales capacity, considering that business actors can indirectly help the government in poverty alleviation, 2) The impact of using marketplaces on Facebook has the potential to support economic growth for business actors. The role of the marketplace is very influential on promotion and marketing, dissemination of information to consumers in meeting needs. In terms of material (economic) welfare, marketpalce users have brought changes to the economy of small and medium-sized businesses in Langsa City, especially in West Langsa District